Assessment of heavy metal levels of Agodi Reservoir in Ibadan, Nigeria - P.O. Ogungbile; J.A. Akande; T.O. Ogunbode; O Odekunle (Journal of Applied Sciences and Environmental Management, 2020)
The quality of water discharged into Agodi Reservoir was determined by the levels of Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn. Water samples were collected from the inlet, centre and outlet locations of the reservoir and their heavy metal contents were determined by standard methods using Atomic Absorption Spectrophotometer (AAS) over a period of twelve (12) months covering both rainy and dry seasons. Test location differences and seasonal variations were examined using ANOVA at P<0.05 to establish any gradient effect associated with pollution dynamics. Results showed no seasonal variations in all the heavy metals except for Co. Also, there is no significant variation in heavy metal concentration between the test locations. The heavy metal profile in Agodi Reservoir, measured in mg/L, was as follows: Mn (64.81) > Fe (43.75) > Zn (23.13) > Cu (12.44) > Co (0.19) > Ni (0.17) > Cd (0.12). Concentrations of Cr and Pb were below detectable level. Compared to WHO recommended limits, Co fell below while others were higher than thresholds. It is concluded that Agodi Reservoir water has a potential environmental hazard unless treated before use.